Presentation - Dossier Teaching History, Women's History and Social Inequalities in Brazil - Kênia Érica Gusmão Medeiros; Gilmária Salviano Ramos; Paula Faustino Sampaio (Revista Eletrônica História em Reflexão, 2020)
The dossier Teaching history, women's history and social inequalities in Brazil is an invitation to a feminist present and future. The work has a set of concrete, purposeful and immediate actions of history teaching within the field of women's history and gender studies. From north to south, from west to east of Brazil, the dossier on screen received articles that are crossed by discussions about the social markers of gender, class and race.